P-ROSC, UB-ROSC, and RACA Scores in Predicting the Return of Spontaneous Circulation in Out-of-hospital Cardiac Arrest: A Retrospective Cohort - Janbavonkij, Tanakorn; Yuksen, Chaiyaporn; Aramvanitch, Kasamon; Sanguanwit, Pitsucha; Laksanamapune, Thanakorn; Jenpanitpong, Chetsadakon; Trainarongsakul, Thavinee; Seesuklom, Suteenun (Archives of Academic Emergency Medicine, 2025)
Introduction: Prehospital Return of Spontaneous Circulation (P-ROSC), Utstein-Based Return of Spontaneous Circulation (UB-ROSC), and Return of Spontaneous Circulation After Cardiac Arrest (RACA) scores have been developed to estimate the likelihood of Return of Spontaneous Circulation (ROSC) in Out-of-hospital cardiac arrest (OHCA). This study aimed to validate and compare these three scoring systems. Methods: A retrospective cohort study was conducted using electronic medical records of OHCA patients transported by Ramathibodi Emergency Medical Service (EMS) from January 2021 to October 2024. We included all OHCA patients aged >18 years who transported by Ramathibodi EMS. RACA, UB-ROSC, and P-ROSC scores were calculated, and ROSC was recorded. The area under the ROC curve (AUC) of each score were calculated to assess predictive accuracy. Results: Among 336 OHCA cases, 94 (27.97%) patients achieved ROSC. The RACA score demonstrated the highest predictive accuracy, with an AUC of 0.77 (95% CI: 0.71–0.82). The UB-ROSC score followed with an AUC of 0.72 (95% CI: 0.66–0.78), while the P-ROSC score had the lowest predictive value with an AUC of 0.64 (95% CI: 0.58–0.70). Calibration analysis indicated that the RACA score aligned most closely with observed outcomes compared to the UB-ROSC and P-ROSC scores. The RACA score exhibited the best overall performance in terms of both discrimination and calibration. Conclusions: Among the three predictive models assessed, the RACA and UB-ROSC scores demonstrated fair predictive accuracy for ROSC in OHCA patients, while the P-ROSC score had poor predictive value.